Six Sigma and patient satisfaction in Orthopaedic Clinic - Zafiropoulos, George (IJRDO - Journal of Social Science and Humanities Research, 2019)
Purpose: Productivity and efficiency are key factors for an improved well-functioning organisation. Six Sigma Methodology uses tools that can help quantify the improvement achieved. Healthcare organisations are known to apply these tools to check quality of their services and patient satisfaction.Design/Methodology/Approach: The study performed at a District General Hospital attempted clarification of reasons influencing the delays observed in Orthopaedic Outpatient Clinic. To achieve it, two audits were performed following managerial and open departmental meetings. The first audit was planned to investigate the potential reasons for the delays. Following organisational alterations according to the findings the second audit would close the loop and analyse the learned lessons using Six Sigma Methodology..Findings: In the initial audit, run for two month, 2110 patients replied, after consenting verbally, to questionnaires asking their opinion of possible reasons influencing their late arrival. Analysis found that their main complaints were parking and the sitting area of the clinic. Six Sigma analysis was performed. After alterations a second audit closed the loop running for similar time period collecting 2530 questionnaires. Significant improvement to patient satisfaction was found on the targeted problems. Further issues resurfaced. The conclusion of the study reinforced the use of Six Sigma as a tool of analysing and controlling the quality in Healthcare.Originality: Applying Six Sigma Methodology as a tool in Health care proven to be important as quality improvement is visible, measurable and everyone is able to understand and follow it.